2017
DOI: 10.5350/sleep.hypn.2017.19.0138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Massage Therapy on Sleep Quality of Patients with End-Stage Renal Disease Undergoing Hemodialysis

Abstract: Sleep disorder is one of the important problems in hemodialysis patients (HPs) that could decrease their life quality. Nowadays, increasing health level of HPs is an important issue regards the flourish statistics of these patients. Some studies have shown that massage therapy reduces back pain, obviate insomnia, make calmness and raise health in HPs due to the release of endorphins. This research was conducted to determine the effects of foot massage on nightly sleep quality of HPs. This experimental study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
1
14
0
3
Order By: Relevance
“…The study by Burbank on the effect of vibration on the value of sleep in RLS patients found that RLS-related sleep disturbance significantly decreased after one month of vibration therapy (36). These findings are consistent with our results, while vibration therapy exerts a positive (37). Moreover, the study by Unal and Akpin, exploring the effect of back massage and plantar reflexology on fatigue and sleep quality in hemodialysis patients indicated that these methods improved sleep quality and fatigue in hemodialysis patients, with plantar reflexology being more effective than lower back and upper back massage (20).…”
Section: Discussionsupporting
confidence: 92%
“…The study by Burbank on the effect of vibration on the value of sleep in RLS patients found that RLS-related sleep disturbance significantly decreased after one month of vibration therapy (36). These findings are consistent with our results, while vibration therapy exerts a positive (37). Moreover, the study by Unal and Akpin, exploring the effect of back massage and plantar reflexology on fatigue and sleep quality in hemodialysis patients indicated that these methods improved sleep quality and fatigue in hemodialysis patients, with plantar reflexology being more effective than lower back and upper back massage (20).…”
Section: Discussionsupporting
confidence: 92%
“…Most studies yielded no data material on bias concealment. One study had insufficient data on attrition rates [ 44 ]. We found no included studies with potential bias in the domain of selective reporting.…”
Section: Resultsmentioning
confidence: 99%
“…Hedges' g of the ten studies [ 8 , 41 44 , 49 , 51 , 62 – 64 ] examined sleep quality following foot reflexology intervention by using different outcome measurement tools such as the Pittsburgh Sleep Quailty Index; the Verran and Snyder-Halpern Sleep Scale; St. Mary's Hospital Sleep Questionnaire; and Richard–Campbell Sleep Questionnaire which were included in our meta-analysis. Hedges' g for the overall effect size was −1.665, and the 95% CI was −2.361 to −0.970 ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…on quality of sleep in patients on hemodialysis realized: foot massage therapy has a positive impact on improving sleep quality in patients on hemodialysis. [23]…”
Section: Discussionmentioning
confidence: 99%